Power flow analysis considering solar road generation - Wei Dai; Bochen Shi; Tengfei Li; HuiHwang Goh; Jinghua Li (Energy Reports, 2022)
To fight against climate change and environmental pollution, the share of renewable energy capacity immensely grows worldwide, especially photovoltaic power. Meanwhile, road transportation develops quickly for the convenience of traveling. Due to abundant solar resources in road transportation and flexible installation of photovoltaic power, solar road generation with huge generation potentials will be a promising solution to alleviate environmental burden in the future. To analyze the influence of solar road integration on power flow, this paper proposes a power flow (PF) analysis method with solar road integration. Based on the photovoltaic model, the solar road generation model coupled with traffic flow is formulated. Two representative scenarios are developed to represent the uncertainties of solar road (i.e., solar irradiation, traffic flow). Finally, the simulation results performed on IEEE 33-bus system under three test cases verify the feasibility and effectiveness of the proposed solar road generation model.